A new approach for energy efficiency in software defined network - Priyadarsini, Madhukrishna; Bera, Padmalochan; Rahman, Mohammad Ashiqur (2018 Fifth International Conference on Software Defined Systems (SDS), 2018)
Software Defined Network(SDN) has evolved as a network paradigm to serve real time traffic with varying requirement in large scale network. The basis of SDN lies on separation of data plane from the control programs providing flexibility to reconfigure the controller with change in requirements. It enables programmability of network control functions and abstraction of underlying architecture for application and services. It also introduces certain challenges towards scalability and performance, security hardening and cross-layer communication. The Performance of SDN depends upon traffic management, load balancing, energy consumption etc. The varying traffic requirements potentially may degrade the performance of the network. So, there is a need of energy efficient optimized solutions for traffic management and load balancing in SDN. In this paper, a framework for energy efficiency in SDN is presented. The operational basis of our framework are introduction of sleep-active mode for energy efficiency and heuristic optimized algorithm for route selection with varying requirements across various domains. We propose an analytic model for power management in a network with above mentioned capabilities. The efficacy of our proposed framework is represented with extensive simulation results which shows approximately 25% reduction in energy consumption for traffic management and load balancing in SDN.